Salmonellae: molecular basis of infection - Miller, Samuel (Henry Stewart Talks, 2009)
Salmonellae, Gram-negative bacteria that cause gastroenteritis and systemic disease or enteric fever, Mechanisms of bacterial pathogenesis include: sensing host environments through a specific receptor, remodeling the bacterial surface, and altering host cells processes, A receptor that recognizes antimicrobial peptides and low pH, Regulation of the structure of lipopolysaccharide, and alteration of the Salmonella-containing phagosome by use of a specialized secretion system that functions to accomplish protein transport to the mammalian cell cytoplasm